2019
DOI: 10.1186/s41100-019-0246-3
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in chronic kidney disease: it is time to reconsider

Abstract: Constipation is highly prevalent in patients with chronic kidney disease (CKD) and is primarily characterized by decreased intestinal motility. This chronic disorder affects the quality of life of patients. However, nephrologist and dialysis clinicians have long had a disproportionately limited understanding of constipation. Accumulating evidence has revealed a relationship between constipation and cardiovascular disease and CKD. The pathogenesis of constipation in CKD patients is multifactorial: decreased phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 96 publications
(143 reference statements)
2
16
0
Order By: Relevance
“…It is in agreement with recent studies that have shown that both drug groups are associated with nocturia [35][36][37] and decreased gastrointestinal motility [19,[38][39][40]. Recent review articles comprehensively analyzed possible pathogenic mechanisms of CKD-related constipation [41,42].…”
Section: Discussionsupporting
confidence: 87%
“…It is in agreement with recent studies that have shown that both drug groups are associated with nocturia [35][36][37] and decreased gastrointestinal motility [19,[38][39][40]. Recent review articles comprehensively analyzed possible pathogenic mechanisms of CKD-related constipation [41,42].…”
Section: Discussionsupporting
confidence: 87%
“…Recognizing abnormalities in these frequencies may assist in disease recognition, optimized patient management and improved outcomes as seen in human medicine. 7…”
Section: Discussionmentioning
confidence: 99%
“…1,4,8,9 Gut dysbiosis and the gut–kidney axis is an emerging area of focus in both human and veterinary medicine. 7,10 Dysbiosis in kidney disease is noted early in the course of disease and has been implicated in altered metabolism of dietary components, altered metabolome, production of uremic toxins and precursors, oxidative stress, chronic inflammation, as well as changes in gut epithelium integrity. 7,11 More recently, experimental models of CKD and clinical studies in uremic patients have started to link gut dysbiosis, uremic metabolites and motility to constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of fibre supplements, stool softeners and probiotics which are confounders when examining stool consistency and frequency, were very low in this cohort. These findings were surprising as both constipation and diarrhoea have been reported as being problematic in this population (Higashihara et al, 2018; Ikee et al, 2019). Our results showing 20% of those on PD reporting constipation and 16% of those on HD is consistent with other studies (Zuvela et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…There is a lack of studies examining whether the prevalence of constipation or diarrhoea increases with the progression of CKD (Ikee et al, 2019). Results from this study suggest that the prevalence is similar for CKD‐ND, HD and PD.…”
Section: Discussionmentioning
confidence: 99%